Prevalence and main risk factors of equine infectious anemia in the southern of Bahia Coast Identity Territory, Brazil - Araújo, José Muniz De; Costa, Joselito Nunes; Ferrao, Iram Da Silva; Ribas, Jorge Raimundo Lins; Nunes, Breno Queiroz; Torres, Paulo Emílio; Mendonça, Ana Paula Abreu [UNESP] (Instituto Biológico, 2023)
The state of Bahia has the third largest equine herd in Brazil, with the horse industry overtaking several sectors of the economy currently. However, animals may be exposed to several pathogenic agents, especially the equine infectious anemia (EIA) virus. EIA is a persistent viral disease with a worldwide distribution and is considered the main infectious disease in horses. Therefore, this study sought data from serological survey EIA in Itapé and Barro Preto municipalities, inserted in the southern Coastal Identity Territory of Bahia, by using the agar gel immunodiffusion test. A total of 1,880 blood serum samples from Equidae older than 6 months were analyzed from 172 properties. The general prevalence of outbreaks was 25.58% (44/172), presenting 40.47% (34/84) in Barro Preto (cocoa zone) and 11.36% (10/88) in Itapé (livestock zone). The prevalence of positive animals in Itapé was 1.01% and in Barro Preto 12.15%. Each assessed property received a questionnaire with emphasis on sanitary management and a booklet containing basic disease information. It was concluded the EIA is endemic in two epidemiologically distinct areas in the Southern Coastal Identity Territory of Bahia, one with a high prevalence in the cocoa zone for both animals and properties, and the other, in livestock zone, with a significantly low prevalence for animals, however also high for properties. Regarding the risk factors, there was a correlation between the species and age of the animals. Mules and the elderly showed a significant association, probably due to the habitat they live in and longer exposure to the virus.
Keywords: anemia; agar gel immunodiffusion; mules; equine; lentivirus